Localized tubercular swelling in the hand masquerading as a ganglion - A rare case report - Nithya Raghunath; Sreekar Harinatha; Kiran Petkar; Sreeharsha Harinatha (Our Dermatology Online, 2012)
Musculoskeletal system involvement in tuberculosis is rare. Especially rare is the involvement of hand. The affected hand can present in different modes ranging from dactylitis to multiple tubercular lesions. Here we present a localized lesion which was initially diagnosed as a ganglion.